Mechanisms of bacterial attachment to roots - Wheatley, R; Poole, P (Oxford University Press, 2018)
The attachment of bacteria to roots constitutes the first physical step in many plant–microbe interactions. These interactions exert both positive and negative influences on agricultural systems depending on whether a growth-promoting, symbiotic or pathogenic relationship transpires. A common biphasic mechanism of root attachment exists across agriculturally important microbial species, including Rhizobium, Agrobacterium, Pseudomonas, Azospirillum and Salmonella. Attachment studies have revealed how plant–microbe interactions develop, and how to manipulate these relationships for agricultural benefit. Here, we review our current understanding of the molecular mechanisms governing plant–microbe root attachment and draw together a common biphasic model.